2012
DOI: 10.2217/pgs.12.161
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Combinations of Immune-Response Genes as Possible Composite Markers of IFN-β Efficacy in Multiple Sclerosis Patients

Abstract: The data obtained provides evidence of the cumulative effect of immune-response genes on IFN-β treatment efficacy. This joint contribution may reflect the additive effect of independent allelic variants and epistatic interactions between some of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…This disagrees with Pulkkinen et al , reported an increased frequency of CCR5 Δ32/Δ32 genotype in MS patients compared with controls. However, in our study, carriage of CCR5 Δ32 allele was associated with a good response to IFN‐β therapy ( P ≤ 0.01), which is in line with a study done by Kulakova et al , they found that CCR5Δ32 allele was correlated with a favorable IFN‐β and an adverse GA responses, thus they could be used as selection tools for the best line of treatment and chemokine system interference might be an effective therapeutic approach in MS.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This disagrees with Pulkkinen et al , reported an increased frequency of CCR5 Δ32/Δ32 genotype in MS patients compared with controls. However, in our study, carriage of CCR5 Δ32 allele was associated with a good response to IFN‐β therapy ( P ≤ 0.01), which is in line with a study done by Kulakova et al , they found that CCR5Δ32 allele was correlated with a favorable IFN‐β and an adverse GA responses, thus they could be used as selection tools for the best line of treatment and chemokine system interference might be an effective therapeutic approach in MS.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the effect of type 1 interferon receptors polymorphisms on the response to IFN‐β treatment, the genomic variations of IFNAR1 and IFNAR2 genes were not associated with IFN‐β treatment response which were consistent with other previous studies .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Glatiramer acetate is suggested to provide specific blocking anti-myelin antibodies activity, and thus address MS pathogenesis, which is associated with breach of the immune tolerance to myelin (Morris-Downes et al, 2002 ). Despite the ambiguous data regarding the limited therapeutic efficacy of this drug (Kulakova et al, 2012 ), glatiramer acetate is widely used for MS therapy. It should be noted that these immune modifying drugs are known for particular low efficacy for treatment of primary, and secondary non-remitting (progressive) forms of MS which are less prevalent than relapsing-remitting form of MS but often associated with more severe clinical symptoms (Gajofatto et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%